2021
DOI: 10.1038/s41598-021-01125-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between antibiotics use and diabetes incidence in a nationally representative retrospective cohort among Koreans

Abstract: Numerous studies have reported that antibiotics could lead to diabetes, even after adjusting for confounding variables. This study aimed to determine the causal relationship between antibiotics use and diabetes in a nationally representative cohort. This retrospective cohort study included adults aged 40 years or older who were enrolled in the Korean National Health Insurance Service-Health Screening Cohort. Antibiotic exposure was assessed from 2002 to 2005 and newly diagnosed diabetes mellitus was determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 39 publications
0
10
0
1
Order By: Relevance
“…CCI was calculated by the diagnoses for crucial comorbidities ( Sundararajan et al, 2004 ; Quan et al, 2005 ). Infectious diseases, which are possible comorbidities related to an antibiotic prescription, were included as covariates using the ICD-10 codes ( Park et al, 2021 ). Infectious diseases were adjusted for five sources of infection in the analysis model, not just one variable.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CCI was calculated by the diagnoses for crucial comorbidities ( Sundararajan et al, 2004 ; Quan et al, 2005 ). Infectious diseases, which are possible comorbidities related to an antibiotic prescription, were included as covariates using the ICD-10 codes ( Park et al, 2021 ). Infectious diseases were adjusted for five sources of infection in the analysis model, not just one variable.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, we carried out sensitivity analyses that determined the association of antibiotic use with dementia risk after excluding patients diagnosed with dementia within the first 1–3 years of follow-up. In other words, we did not consider new cases of dementia for those diagnosed within the first 3 years of follow-up to address protopathic bias ( Park et al, 2021 ). We also conducted sensitivity analyses by shifting the index date to 1 year later to minimize possible confounding effects caused by the drug exposure period after the defined index date ( Kim et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…In the research, the non-users of antibiotics or the lowest users of antibiotics were used as reference groups. The group with the smallest number of antibiotic users was utilized as a reference when adjusting for indications of antibiotic use to reduce the possibility of multicollinearity [9].…”
Section: Key Variablesmentioning
confidence: 99%
“…The possibility of an association between antibiotic usage and various types of cancer, including prostate cancer, has been suggested in previous studies [6][7][8]. Previous cohort studies have reported that long-term antibiotic exposure may be associated with the risk of other diseases such as diabetes, dementia, and obesity [9][10][11]. The effects of antibiotics on gut microbiota diversity reduction and alteration have been revealed [12].…”
Section: Introductionmentioning
confidence: 99%
“…We considered covariates, including age, sex, residence, household income, smoking, alcohol consumption, physical activity, body mass index (BMI; kg/m 2 ), total cholesterol (mg/dL), systolic blood pressure (mmHg), fasting serum glucose (mg/dL), Charlson comorbidity index (CCI), the number of healthcare visit, and infectious diseases. To adjust the indication of antibiotic use, we included intra-abdominal infections; urinary tract infections; intestinal infectious diseases; skin, soft tissue, bone, and joint infections; and others (22) (Supplementary Table 2).…”
Section: Covariatesmentioning
confidence: 99%